Influence of organizational culture and self efficacy on employee performance (PT Java Indosinergi Creative) - Ahmad Dicky Ariyanto; Achmad Sani Supriyanto (Institute of Computer Science (IOCS), 2022)
In line with the development of the increasingly global business world, the management of an organization must be carried out professionally and productively, so that the organization can still maintain survival and continue to develop along with the times. Every effort in achieving company goals cannot be separated from the role of human resources. Human resources are considered important because they can affect the efficiency and effectiveness of the organization, and are the main expenses of the organization in carrying out its activities. Quantitative research methods Research methods based on the philosophy of positivism, are used to research on specific populations or samples with the aim of testing established hypotheses. This type of research uses explanatory research. The result of this study is that Organizational Culture has a positive and significant effect on Employee Performance at PT Java Indosinergi Creative, Self efficacy has a positive and significant effect on Employee Performance at PT Java Indosinergi Creative, Organizational Culture has a positive and significant effect on work motivation at PT Java Indosinergi Creative, Self efficacy has a positive and significant effect on job satisfaction at PT Java Indosinergi Creative.